Pembentukan KEPITING (Kelas Pijat Balita Anti Stunting) melalui Pemberdayaan Ibu dalam Mengoptimalkan Gizi dan Nafsu Makan Balita di desa Getas Wonopringgo Pekalongan: The Formation of KEPITING (Anti-Stunting Toddler Massage Class) through the Empowerment of Mothers in Optimizing Nutrition and Appetite of Toddlers in Getas Wonopringgo Village Pekalongan - Ersila, Wahyu; Prafitri, Lia Dwi; Sulistiani, Ria Purnawian; Erlinda, Talitha Rahma; Pratista, Agni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Stunting remains a serious health problem in Indonesia, including in Pekalongan Regency, where the prevalence increased from 11.1% to 11.3% in 2023. Getas Village, Wonopringgo District, recorded the highest stunting rate at 45.16%. Previous efforts focused on providing supplementary feeding without an integrated education program, whereas outreach from the integrated health post has not been optimal. This condition has resulted in mothers' low knowledge regarding stunting prevention and stimulating toddlers' appetite. The KEPITING (Anti-Stunting Toddler Massage Class) program is designed to empower mothers to enhance their understanding of nutrition and parenting, as well as improve their attitudes, motivation, and skills in infant massage, promoting the nutritional status and appetite of toddlers. Implementation methods include outreach, toddler massage practice, demonstrations of making simple, nutritious supplementary foods, such as MODISCO (Modified Dietetic Skim Milk and Coconut Oil), and appetite massage assistance. The results of the activity showed an increase in average body weight of 540 grams, an average height of 1.7 cm, a toddler appetite p-value of 0.001, knowledge about toddler nutrition p-value of 0.009, knowledge of parenting patterns p-value of 0.017, maternal attitudes p-value of 0.028, maternal motivation p-value of 0.002, and maternal skills p-value of <0.001. In conclusion, KEPITING can strengthen the role of mothers in preventing stunting through educational approaches and direct practice, as well as serving as a community-based intervention model that is expected to be replicated in other areas of Pekalongan.